Security and Cryptography for Networks : 10th International Conference, SCN 2016, Amalfi, Italy, August 31-September 2, 2016, Proceedings /: 10th International Conference, SCN 2016, Amalfi, Italy, August 31-September 2, 2016, Proceedings. (2016) - Unknown
No abstract available